2020
DOI: 10.1186/s12912-020-00454-6
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating oral health care education in undergraduate nursing curricula - a systematic review

Abstract: Background: The recognised relationship between oral health and general health, the rapidly increasing older population worldwide, and changes in the type of oral health care older people require have raised concerns for policymakers and health professionals. Nurses play a leading role in holistic and interprofessional care that supports health and ageing. It is essential to understand their preparation for providing oral health care. Objective: To synthesise the evidence on nursing students' attitudes towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 55 publications
(103 reference statements)
3
36
0
1
Order By: Relevance
“…In this study, the educational needs of nurses in oral and dental health of hospitalized patients were identified. According to some studies, nurses are not satisfied with the health of the mouth and there is a need for training [ 30 , 31 ]. Therefore, there is a need for training and education.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the educational needs of nurses in oral and dental health of hospitalized patients were identified. According to some studies, nurses are not satisfied with the health of the mouth and there is a need for training [ 30 , 31 ]. Therefore, there is a need for training and education.…”
Section: Discussionmentioning
confidence: 99%
“…Haghighi et al reported a remarkable improvement in the plaque index along with effective reduction of VAP occurrence with oral hygiene management while controlling the cuff pressure of the respiratory tract [41]. However, considering that little oral health education is included in the curriculum and that interprofessional education using materials studied by dental hygienists or dentists is poorly performed [63], it is difficult to achieve effective intervention results solely by nurses, and it is necessary to approach this oral management from a dental perspective.…”
Section: Tooth Brushing Methodsmentioning
confidence: 99%
“…In addition to specific ohr-interRAI training programs, the attention for oral health in the training of healthcare students needs to be increased as well. Current curricula of nursing students often cover the topic insufficiently, but it was repeatedly shown that particularly inter-professional education is suited to improve oral health-related knowledge, competence, and confidence among nursing students [54][55][56][57].…”
Section: Interpretation Of the Results And Future Prospectsmentioning
confidence: 99%